2014
DOI: 10.1371/journal.pone.0111967
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Agency and Ownership: The Intentional Binding and Rubber Hand Illusion Paradigm Combined

Abstract: The sense of agency (SoA) refers to the phenomenal experience of initiating and controlling an action, whereas the sense of ownership (SoO) describes the feeling of myness an agent experiences towards his or her own body parts. SoA has been investigated with intentional binding paradigms, and the sense of ownership (SoO) with the rubber-hand illusion (RHI). We investigated the relationship between SoA and SoO by incorporating intentional binding into the RHI. Explicit and implicit measures of agency (SoA-quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
101
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 52 publications
13
101
6
Order By: Relevance
“…A 10-item questionnaire was adopted from previous studies3233 and used for the assessment of subjective experience (Table 1). The questions were read by the experimenter at the end of each block and the participants indicated their level of agreement on a 7-point Likert scale, ranging from −3 (“totally disagree”) to +3 (“totally agree”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 10-item questionnaire was adopted from previous studies3233 and used for the assessment of subjective experience (Table 1). The questions were read by the experimenter at the end of each block and the participants indicated their level of agreement on a 7-point Likert scale, ranging from −3 (“totally disagree”) to +3 (“totally agree”).…”
Section: Methodsmentioning
confidence: 99%
“…We predicted that an embodied feedback signal closely resembling the mental act performed should be more intuitive for neurofeedback operation than non-embodiable feedback and therefore should also lead to a better NF-MIT performance18. As an artificial hand is known only to induce SoO, if it is placed in an anatomically-congruent position323334, we tested the hypothesized benefit of embodied feedback by comparing neurofeedback delivered by the artificial hand in a congruent position with that delivered in an incongruent position. We also asked whether NF-MIT performance and SoA depend on the validity of the neurofeedback signal.…”
mentioning
confidence: 99%
“…Lastly, Riemer, Kleinböhl, Hölzl, and Trojan (2013) report equally strong subjective ratings for active-movements and visuotactile-stimulated conditions and both Tsakiris et al (2006) and Ehrsson (2012, 2014) found no difference in ownership ratings or proprioceptive drift between three conditions that differed in activity. To add to the confusion, Braun, Thorne, Hildebrandt, and Debener (2014) found some associations and some double-dissociations between sense of agency and sense of ownership.…”
Section: Ownership and Agencymentioning
confidence: 99%
“…Agency on the other hand is the feeling of directly causing changes in the environment. With contradicting findings, the correlation of agency and ownership is still unclear [9,13,31,32,59].…”
Section: Self-attribution: Ownership and Agencymentioning
confidence: 99%
“…• Anatomical plausibility: the artificial limb must be in a plausible posture (position and orientation) with respect to the body [9,14,18,30,31,32,34,48,55].…”
Section: Body Ownership Illusions (Bois)mentioning
confidence: 99%